2021
DOI: 10.3389/fendo.2021.639592
|View full text |Cite
|
Sign up to set email alerts
|

Low-Dose Aspirin Prevents Kidney Damage in LPS-Induced Preeclampsia by Inhibiting the WNT5A and NF-κB Signaling Pathways

Abstract: Preeclampsia (PE) is a serious pregnancy-related disease, and patients usually present with a high inflammatory response. Previous studies have suggested that aspirin (ASP) may have a role in alleviating the pathogenesis of preeclampsia. However, whether ASP can improve kidney damage and the mechanism for improving it is currently unclear. Here we optimized a lipopolysaccharide (LPS)-induced PE mouse model to identify the role of ASP in renal protection. We found that ASP treatment ameliorated LPS-induced rena… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 52 publications
0
11
0
Order By: Relevance
“…Low-dose aspirin was used for its clearly demonstrated anti-thrombotic action, as it could reduce or dampen platelet aggregation, with the aim of preventing micro- or macro-thrombosis during the initial stage of the disease [ 20 , 21 ]. The use of a gastro-protector was considered to avoid the cumulative dangerous effects of the anti-inflammatory agent and the anti-aggregating drug on the stomach, including stress ulceration and gastrointestinal bleeding [ 22 ].…”
Section: Introductionmentioning
confidence: 99%
“…Low-dose aspirin was used for its clearly demonstrated anti-thrombotic action, as it could reduce or dampen platelet aggregation, with the aim of preventing micro- or macro-thrombosis during the initial stage of the disease [ 20 , 21 ]. The use of a gastro-protector was considered to avoid the cumulative dangerous effects of the anti-inflammatory agent and the anti-aggregating drug on the stomach, including stress ulceration and gastrointestinal bleeding [ 22 ].…”
Section: Introductionmentioning
confidence: 99%
“…Polonikov et al [211], Chida et al [212], Yamada et al [213], Zhang et al [214], Kawarazaki et al [215], Ueda et al [216], Bao et al [217], Leng et al [218], Taghvaei et al [219], Norling et al [220], Brown et al [221], Singh et al [222], Liu et al [223], Nie et al [224], Liu et al [225], Sharma et al [226], Liu et al [227], Jain et al [228], Novoyatleva et al [229], Yu et al [230], Sahoo et al [231], Gamboa et al [232], Zeng et al [233], Zabini et al [234], Olivi et al [235], Liu et al [236], Nabrdalik et al [237], Katayose et al [238], Topchieva et al [239], Onal et al [240], Speirs et al [241], Novelli et al [242], Le Hiress et al [243], Chang et al [244], Deng et al [245], Wang et al [246], Dhande et al [247], Yu et al [248] and Li et al [249] showed that CYP2J2, BMPR1B, ROS1, SCN7A, WNT5A, HSD11B2, CYP24A1, WNK3, PPARGC1A, IGF1, OSR1, TLR3, BMP7, POSTN (periostin), ITGB3, THBS1, FLNA (filamin A), TRPC6, SELP (selectin P), VCL (vinculin), NOTCH2, F2RL3, LRP1, CLU (clusterin), SMAD3, PEAR1, MYH9, TGFB1, PDGFA (platelet derived growth factor subunit A), IL6R, TIMP1, TNFRSF1B, CD47, CD74, VCAN (versican), IRF7, NOTCH1, STIM1, CXCR4 and PDE5A expression can be associated with hypertension progression, but these genes might be novel targets for GDM. ROS1 [250], WNT2 [251], PHLDA2 [252], WNT5A [253], HSD11B2 [254], CLDN1 [255], CYP24A1 [256], HRG (histidine rich glycoprotein) [257], TLR3 [258], THBS1 [259], TRPC6 [260], SELP (selectin P) [261], CLU (clusterin) [262], CDKN1A [263], ITGB1 [264], HLA-E [265], IL6R [266], TIMP1 [267], SERPINA1 [268], CD74 [269], PANX1 [270], STIM1 [271] and CXCR4 [272] were revealed to be correlated with disease outcome in patients with preeclampsia. Previously reported studies h...…”
Section: Discussionmentioning
confidence: 99%
“…Low-dose aspirin has been widely used as an antithrombotic agent. Its use in SARS-CoV-2 infection could help reduce or dampen platelet hyper-aggregation, which may be caused by the binding of the virus spike to platelet ACE2 receptors, and it could be used to prevent thrombosis during the early phase of COVID-19 [ 97 , 98 ].…”
Section: Low-dose Aspirinmentioning
confidence: 99%